ANALISA POTENSI KECELAKAAN KERJA PADA PT. PLN (PERSERO) SUMBAWA MENGGUNAKAN METODE HAZARD AND OPERABILITY STUDY (HAZOP) - Resti Ariyani; Ryan Suarantalla; Ismi Mashabai (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2021)
Human Resources (HR) is an important element in a company. For this reason, HR must be properly maintained as an invaluable asset in the company. A good company will provide facilities to maintain the safety and comfort of HR. Companies usually will provide guidelines for working in a company that have been standardized so that the job becomes easy to do. These guidelines are often referred to as occupational health and safety (K3) guidelines. One of the companies implementing K3 is PT. PLN (Persero) Sumbawa. Such a great threat can occur in this company due to the vast work field that there are several high work risks such as falling from a height or being electrocuted. Due to high hazards, risk management is needed which includes hazard identification to determine risks that give rise to occupational accident hazards, analyze potential hazards, assess risks, and make recommendations to reduce the occurrence of work accidents. So it is necessary to conduct research to identify and suggest improvements to working conditions to minimize hazards. This study uses the Hazard and Operability Study (HAZOP), which is a method used to identify and analyze hazards so that the processes that take place in a system can run smoothly and safely.